EFEKTIFITAS REGULASI PENGEMBANGAN PARIWISATA BUDAYA BERBASIS INDUSTRI SILAT DI KOTA MADIUN, JAWA TIMUR PERSPEKTIF TEORI SISTEM HUKUM - Nugroho, Sigit Sapto; Haryani, Anik Tri; Purnama, Taufiq Yuli (Jurnal Ilmiah Dinamika Hukum, 2024)
This study aims to determine the Madiun Mayor's policy in developing pencak silat as cultural tourism and at the same time to determine the effectiveness of the Madiun City government's policy in developing cultural tourism based on the silat industry in the perspective of Lawrence M. Friedman's legal system theory. The author uses normative legal research methods. Based on the results of the research, it is known that the Madiun City government develops the potential of pencak silat based on smart city through a smart branding roadmap which includes two programmes, namely the pencak silat experience tourism development programme and the pencak silat friend programme. In addition, the City Government through Disbudparpora also manages pencak silat through art performances and intercollegiate competitions. The effectiveness of the Madiun City Government's policy in developing cultural tourism based on the silat industry in the perspective of Lawrence M. Friedman's legal system theory states that legal effectiveness is influenced by three elements of the legal system, namely the structure of law, the substance of the law and legal culture. Based on this theory, the concept of developing Madiun City Pendekar cultural tourism based on the martial arts industry can be directed through the development of tourism policies based on pencak silat culture, synergy between the Madiun City Government and the implementing apparatus and building public awareness.